Gestational age estimation from ultrasound fetal biometrics in China - J.F. Sun; L.J. Zhang; L.Q. Cui; X.D. Luo; G.H. He; X.J. Dong; L. He; J.H. Zhang; J.H. Sun; G. Chen; Y. Lv; L.Y. Liu (IMR Press, 2020)
Objective: To establish a new gestational age estimation equation in China and compare them with commonly used equations of 2017 and 1984. Methods: A prospective cross-sectional study was performed in 3208 fetuses between 15 and 40 weeks of gestation. The following biometric variables were recorded: biparietal diameter, head circumference, abdominal circumference, and femur length. Women with a certain gestational age were confirmed by the last menstrual period with a regular cycle of 26-32 days. Subsequently, a mixed regression model was used for regression analysis for the estimation equation of gestational age. Additionally, validation set was used to verify the accuracy of the equation. Estimation error was defined as the mean square deviation between the estimation equation and observed gestational age and its accuracy was compared with that analyzed by Hadlock and National Institute of Child Health and Human Development (NICHD) equations. Results: The gestational age estimation errors of the new equation are within 9.62 days from 15 to 20 weeks, 7.90 days from 21 to 25 weeks, 11.76 days from 26 to 30 weeks, 9.35 days from 31 to 35 weeks, and within 11.30 days from 36 to 40 weeks of gestation. Compared to the results evaluated by the Hadlock and NICHD equations, the estimation of the new equation has significantly improved gestational age determination in the second and third trimesters. Conclusions: The estimation results of the new equation is superior to those of the Hadlock and NICHD equations and provides more accurate results for gestational age estimation with ultrasonic examination.